Polyanion positive electrode material and preparation method and application thereof
The preparation of polyanionic positive electrode material with molecular-grade carbon coating through hydrothermal reaction and carbonization reaction has solved the problem of poor electronic conductivity and significantly improved the electrochemical performance and cyclic stability.
Patent Information
- Application Number
- CN202411684065.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-04
AI Technical Summary
Polyanionic positive electrode materials have poor electron conductivity in sodium ion batteries, resulting in large electrochemical polarization and short cycle life.
By performing hydrothermal reactions in a solvent, precursors are prepared using iron, phosphorus, sodium, titanium and carbon sources, and carbonization reactions are carried out under the protection of an inert gas to form a polyanionic positive electrode material with molecular-grade carbon coating.
It improves the conductivity and ion/electron transfer efficiency of polyanionic cathode materials, reduces electrochemical polarization, and significantly improves the electrochemical performance and cyclic stability of the materials.
Smart Images

Figure CN119551646A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a polyanion positive electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of new generation energy networks and devices, secondary batteries with excellent performance have received much attention from researchers. Among them, lithium-ion batteries, as a secondary battery that has been widely studied and applied, play a leading role in the power supply of portable mobile devices.
[0003] However, with the growth of demand and the change in the supply and demand of lithium resources, researchers have gradually turned their attention to sodium-ion batteries, which are low-cost, abundant in resources, and easy to obtain. At the same time, they have similar working modes and production and processing methods as lithium-ion batteries. Although sodium-ion batteries and lithium-ion batteries have similar working modes, sodium-ion batteries can hardly use the same electrode materials as lithium-ion batteries due to the different ionic radii of sodium ions and lithium ions.
[0004] Among the many sodium-ion battery electrode materials, polyanion cathodes have the advantages of low cost and good stability, and are very promising cathode materials in the field of sodium-ion batteries. However, they have the problem of poor electronic conductivity, which leads to large electrochemical polarization and short cycle life in actual use. Based on this, it is very important to develop new methods to improve the electrochemical performance of this material.
[0005] In order to overcome these problems, carbon coating and nano-sizing are commonly used solutions. Although these two methods have overcome the problem of slow charge transfer rate to a certain extent, they will reduce their compaction density and specific capacity to a certain extent, which is not conducive to their practical application.
[0006] Therefore, it is necessary to develop a polyanion cathode material with simple preparation process, excellent cycle stability and reversible specific capacity performance. Summary of the invention
[0007] In order to solve at least one of the above technical problems, the present invention provides a polyanion positive electrode material and a preparation method and application thereof.
[0008] As one aspect, the present invention provides a method for preparing a polyanion positive electrode material, comprising: in a solvent, an iron source, a phosphorus source, a sodium source, a titanium source, and a carbon source undergo a hydrothermal reaction, and the reaction product is freeze-dried to prepare a precursor; under the protection of an inert gas, the precursor undergoes a carbonization reaction to prepare a polyanion positive electrode material; wherein the titanium source is selected from an organic titanium compound or a polymer of an organic titanium compound.
[0009] In some embodiments of the present invention, the ratio of the amount of iron, phosphorus, sodium, titanium and carbon in the iron source, phosphorus source, sodium source, titanium source and carbon source is (2.7~2.95):4:(4~4.3):(0.05~0.3):(0.4~0.8).
[0010] In some embodiments of the present invention, the general formula of the organic titanium compound is as shown in formula (I):
[0011]
[0012] Among them, R 1 , R 2 , R 3 , R 4 Each is independently selected from substituted or unsubstituted C2-C10 hydrocarbon groups; or, the organic titanium compound is titanium acetylacetonate.
[0013] In some embodiments of the present invention, wherein R 1 , R 2 , R 3 , R 4 Each independently selected from butyl, isopropyl, tert-butyl,
[0014] Ethyl.
[0015] In some embodiments of the present invention, the titanium source includes at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium acetylacetonate, titanium tert-butoxide, isopropyl tri(dioctylphosphoyl) titanate, tetrabutyl titanate tetramer, di(triethanolamine) diisopropyl titanate, and tetraethyl titanate.
[0016] In some embodiments of the present invention, the iron source includes at least one of ferrous oxalate and ferrous chloride; and / or the phosphorus source includes at least one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate; and / or the carbon source includes at least one of glucose, sucrose, and fructose; and / or the sodium source includes at least one of sodium carbonate, sodium oxalate, and sodium acetate.
[0017] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 120-260°C, and the time is 6-36 hours; and / or the temperature of the carbonization reaction is 520-1000°C, and the time is 4-12 hours; and / or the solvent includes at least one of a binary mixture of alcohol and water and a binary mixture of ketone and water; preferably, the alcohol includes at least one of methanol, ethanol, and butanol, and the ketone is acetone.
[0018] As another aspect, the present invention provides a polyanion positive electrode material, which is obtained by the above-mentioned preparation method; in the polyanion positive electrode material, the content of titanium element is 1-10%.
[0019] As yet another aspect, the present invention provides a positive electrode plate, which comprises the above-mentioned polyanion positive electrode material.
[0020] As yet another aspect, the present invention provides an electrochemical energy storage device, which includes the above-mentioned positive electrode plate.
[0021] In some embodiments of the present invention, the electrochemical energy storage device includes any one of a sodium ion battery, a lithium sodium dual ion battery, a potassium sodium dual ion battery, and a sodium ion capacitor.
[0022] The technical solution provided by the embodiment of the present invention has the following advantages:
[0023] In the preparation method of the polyanion positive electrode material provided by the present invention, the organic titanium compound mainly acts as an in-situ dopant, a morphology regulator and a titanium source. Specifically, in the hydrothermal reaction of preparing the precursor, the titanium (Ti) element in the organic titanium compound uniformly replaces the iron (Fe) element in-situ; and the substituted or unsubstituted hydrocarbon group in the organic titanium compound fully plays the role of a morphology regulator to promote its secondary growth.
[0024] The preparation method of the polyanion positive electrode material provided by the present invention is based on the introduction of a titanium source, titanium doping is introduced in situ, and since the organic precursor in the organic titanium source is evenly distributed between the elements during the reaction, a carbon film is formed in situ after high-temperature carbonization, thereby achieving molecular-level carbon coating of the target positive electrode material, promoting the formation of a spherical structure, and bulk phase doping can improve the conductivity and ion / electron transmission efficiency of the polyanion positive electrode material, effectively reducing the electrochemical polarization of the polyanion positive electrode material during the energy storage process, thereby significantly improving the electrochemical performance of the polyanion positive electrode material. In addition, in the preparation process of the precursor, due to the freeze-drying method for drying, the prepared precursor better maintains the coordination between the titanium source and the iron ion in the hydrothermal reaction, which helps the precursor to have better uniformity; thereby further improving the uniformity of the carbon coating during the carbonization reaction, and further improving the uniformity and purity of the polyanion positive electrode material.
[0025] The polyanion cathode material obtained by the preparation method provided by the present invention has the characteristics of uniform carbon layer structure. The prepared polyanion cathode material can improve the conductivity of the cathode material, accelerate the migration of electrons and ions, and enhance the energy storage performance of the cathode material.
[0026] The preparation method of the polyanion positive electrode material provided by the present invention has the characteristics of simple process and strong scalability, and has great application prospects and research value in the practical application field of sodium ion batteries.
[0027] The polyanion positive electrode material obtained by the preparation method provided by the present invention is applied to an electrochemical energy storage device and has more excellent cycle stability and reversible specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0030] Figure 1 The XRD pattern of the polyanion positive electrode material prepared in Example 1 of the present invention;
[0031] Figure 2 This is the XPS graph of the polyanion cathode material prepared in Example 1 of the present invention;
[0032] Figure 3 This is a SEM image of the polyanion cathode material prepared in Example 1 of the present invention;
[0033] Figure 4 The XRD pattern of the polyanion positive electrode material prepared in Example 2 of the present invention;
[0034] Figure 5 XRD diagram of the positive electrode material prepared in Comparative Example 1 of the present invention;
[0035] Figure 6 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present invention;
[0036] Figure 7 XRD diagram of the positive electrode material prepared in Comparative Example 1 of the present invention;
[0037] Figure 8 The charge and discharge curve of the sodium ion battery prepared by the polyanion positive electrode material obtained in Example 1 of the present invention;
[0038] Fig. 9 The charge and discharge curve of the sodium ion battery prepared by the positive electrode material obtained in Comparative Example 1 of the present invention;
[0039] Fig.10This is a charge and discharge curve diagram of a sodium ion battery prepared using the positive electrode material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0040] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0042] According to an embodiment of one aspect of the present invention, a method for preparing a polyanion positive electrode material is provided, comprising: in a solvent, an iron source, a phosphorus source, a sodium source, a titanium source, and a carbon source undergo a hydrothermal reaction, and the reaction product is freeze-dried to prepare a precursor; under the protection of an inert gas, the precursor undergoes a carbonization reaction to prepare a polyanion positive electrode material; wherein the titanium source is selected from an organic titanium compound or a polymer of an organic titanium compound.
[0043] In the preparation method of the polyanion positive electrode material of the embodiment of the present invention, the role of the organic titanium compound or the polymer of the organic titanium compound is mainly to act as an in-situ dopant, morphology regulator and titanium source. While introducing titanium doping and molecular-level carbon coating in situ, the formation of the spherical structure of the polyanion positive electrode material is promoted. Bulk doping can improve the conductivity and ion / electron transmission efficiency of the polyanion positive electrode material, effectively reduce the electrochemical polarization of the polyanion positive electrode material during the energy storage process, thereby significantly improving the electrochemical performance of the polyanion positive electrode material.
[0044] In some embodiments of the present invention, a method for preparing a polyanion positive electrode material comprises: (1) uniformly mixing an iron source, a phosphorus source, a sodium source, a titanium source, a carbon source, and a solvent in a certain proportion, and then transferring them into a reactor to undergo a hydrothermal reaction at a high temperature, and cooling, filtering, washing, drying, and other operations on the reaction product to obtain a precursor; (2) subjecting the precursor obtained in step (1) to a carbonization reaction in a solid phase sintering technology to obtain a polyanion positive electrode material.
[0045] In some embodiments of the present invention, in step (1), the organic titanium compound or the polymer of the organic titanium compound comprises an organic titanate compound.
[0046] In some embodiments of the present invention, in step (1), the organic titanium compound or the polymer of the organic titanium compound includes at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium acetylacetonate, titanium tert-butoxide, isopropyl tri(dioctylphosphoyl) titanate, tetrabutyl titanate tetrapolymer, di(triethanolamine) diisopropyl titanate, tetraethyl titanate and the like.
[0047] In some embodiments of the present invention, in step (1), the iron source includes at least one of ferrous oxalate, ferrous chloride, and the like.
[0048] In some embodiments of the present invention, in step (1), the phosphorus source includes at least one of ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and the like.
[0049] In some embodiments of the present invention, in step (1), the carbon source includes at least one of glucose, sucrose, fructose, etc.
[0050] In some embodiments of the present invention, in step (1), the sodium source includes at least one of sodium carbonate, sodium oxalate, sodium acetate, etc.
[0051] In some embodiments of the present invention, in step (1), the ratio of the amount of iron, phosphorus, sodium, titanium and carbon in the raw materials of iron source, phosphorus source, sodium source, titanium source and carbon source is (2.7-2.95):4:(4-4.3):(0.05-0.3):(0.4-0.8); for example, the ratio of the amount of the substance can be 2.71:4:4.12:0.061:0.43, 2.76:4:4.18:0.094:0.49, 2.83:4:4.21:0.18:0.64, 2.89:4:4.26:0.21:0.71, 2.91:4:4.28:0.28:0.76, etc.
[0052] In some embodiments of the present invention, in step (1), the solvent includes at least one of a binary mixture of alcohol and water and a binary mixture of ketone and water; wherein the alcohol includes any one of methanol, ethanol, butanol, etc.; and the ketone is acetone. Preferably, the alcohol and water are prepared in a volume ratio of 1:1; and the ketone and water are prepared in a volume ratio of 1:1.
[0053] In some embodiments of the present invention, in step (1), preferably, the water is deionized water.
[0054] In some embodiments of the present invention, in step (1), the hydrothermal reaction temperature is 120-260°C, for example, it can be 126°C, 168°C, 183°C, 218°C, 246°C, 258°C, etc., and the hydrothermal reaction time is 6-36h, for example, it can be 6.9h, 11.8h, 21.9h, 26.2h, 29.7h, 31.3h, 35.6h, etc.
[0055] In some embodiments of the present invention, in step (2), the temperature of the carbonization reaction is 520-1000°C, for example, it can be 539°C, 686°C, 795°C, 836°C, 967°C, 998°C, etc., and the carbonization time is 4-12h, for example, it can be 4.3h, 6.9h, 8.3h, 10.1h, 11.9h, etc.
[0056] In some embodiments of the present invention, the chemical composition of the polyanion cathode material prepared in step (2) is Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 (NFPP), and the element Ti accounts for 1-10% of the total mass of the polyanion positive electrode material elements, for example, it can be 1.3%, 2.8%, 4.3%, 6.2%, 8.1%, 9.6%, etc.
[0057] In some embodiments of the present invention, a method for preparing a polyanion cathode material comprises the following steps:
[0058] S1. Dispersing an iron source, a titanium source, a phosphorus source, a sodium source, and a carbon source in a mixed solvent consisting of deionized water and ethanol in a certain proportion; wherein the volume ratio of deionized water to ethanol is (V water / V ethanol = 1:1), transferring the mixture into a reaction kettle, and causing a hydrothermal reaction under high temperature and high pressure to obtain a mixture;
[0059] S2. Cooling, filtering, washing, drying and the like the mixture obtained in step S1 to obtain a yellow dry powder precursor.
[0060] S3. The yellow dry powder precursor obtained in step S2 is treated by high-temperature solid-phase sintering technology. Under the protection of inert gas, the precursor is heated to undergo a high-temperature carbonization reaction, so that the precursor is converted into a polyanion positive electrode material.
[0061] In order to further illustrate the effect of the present invention, specific embodiments are used for illustration below.
[0062] 1. Preparation of positive electrode materials
[0063] Example 1
[0064] The method for preparing a polyanion positive electrode material using tetraethyl titanate as a titanium source comprises the following steps:
[0065] S1. Dissolve 0.4 mmol of ammonium dihydrogen phosphate, 0.27 mmol of ferrous oxalate, 0.03 mmol of tetraethyl titanate, 0.2 mmol of sodium carbonate and 0.01 mmol of glucose in a mixed solvent consisting of 100 mL of ethanol and deionized water (wherein the volume ratio of deionized water to ethanol is 1:1), transfer the mixture into a reactor, and perform a hydrothermal reaction at 180° C. for 12 h to obtain a mixture.
[0066] S2. The mixture obtained in step S1 is cooled at room temperature, filtered, washed with deionized water, and dried at 100° C. to obtain a yellow dry powder precursor.
[0067] S3, heating the yellow dry powder precursor prepared in step S2 at 700°C for 2h under argon protection to obtain Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 Positive electrode material.
[0068] S4, the polyanion Na prepared in step S3 4 Fe 3 (PO 4 ) 2 P 2 O 7 The positive electrode materials were subjected to XRD, XPS and SEM tests, and the test results were as follows: Figure 1 , Figure 2 and Figure 3 shown.
[0069] according to Figures 1 to 3 The data analysis can draw the following conclusions:
[0070] (1) Figure 1 As shown, the obtained sample Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 The positive electrode material is pure phase NFPP material.
[0071] (2) Figure 2 As shown, an obvious Ti 2p peak can be observed, indicating the successful doping of Ti element.
[0072] (3) Figure 3 As shown, the obtained Na 4 Fe3 (PO 4 ) 2 P 2 O 7 The positive electrode material is a regular spherical material.
[0073] Example 2
[0074] The method for preparing a polyanion positive electrode material using tetraisopropyl titanate as a titanium source comprises the following steps:
[0075] S1. Dissolve 0.4 mmol sodium dihydrogen phosphate, 0.28 mmol ferrous chloride, 0.02 mmol tetraisopropyl titanate, 0.01 mmol sodium acetate, and 0.006 mmol sucrose in 80 mL of a mixed solvent consisting of deionized water and acetone (wherein the volume ratio of deionized water to acetone is 1:1), transfer the mixture into a reactor, and perform a hydrothermal reaction at 200° C. for 24 hours to obtain a mixture.
[0076] S2. The mixture obtained in step S1 is cooled at room temperature, filtered, washed with deionized water, and dried at 100° C. to obtain a yellow dry powder precursor.
[0077] S3, heating the yellow dry powder precursor powder prepared in step S2 at 600°C under nitrogen protection for 6 hours to obtain Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 Cathode material (NFPP cathode material).
[0078] S4, the polyanion Na prepared in step S3 4 Fe 3 (PO 4 ) 2 P 2 O 7 The positive electrode material is subjected to XRD test, and the test results are as follows Figure 4 shown.
[0079] according to Figure 4 The data analysis can draw the following conclusions: Figure 4 As shown, the obtained product Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 The positive electrode material (NFPP positive electrode material) is a pure phase NFPP material.
[0080] Comparative Example 1
[0081] The method for preparing a polyanion positive electrode material using an inorganic titanium salt as a titanium source comprises the following steps:
[0082] S1. Dissolve 0.4 mmol of ammonium dihydrogen phosphate, 0.27 mmol of ferrous oxalate, 0.03 mmol of titanium tetrachloride, 0.2 mmol of sodium carbonate and 0.01 mmol of glucose in a mixed solvent consisting of 100 mL of ethanol and deionized water (wherein the volume ratio of deionized water to ethanol is 1:1), transfer the mixture into a reactor, and perform a hydrothermal reaction at 180° C. for 12 hours to obtain a mixture.
[0083] S2. The mixture obtained in step S1 is cooled at room temperature, filtered, washed with deionized water, and dried at 100° C. to obtain a yellow dry powder precursor.
[0084] S3. The dry powder precursor prepared in step S2 is heated at 700° C. for 2 h under argon protection to obtain a polyanion positive electrode material.
[0085] S4, the polyanion positive electrode material prepared in step S3 is subjected to XRD test and SEM test respectively, and the test results are as follows: Figure 5 , Figure 6 shown.
[0086] according to Figure 5 and Figure 6 The data analysis can draw the following conclusions:
[0087] (1) Figure 5 As shown, if the organic titanium salt is replaced by the inorganic titanium source in the same amount, its crystal composition is impure and there is an obvious impure phase.
[0088] (2) Figure 6 As shown, if the organic titanium salt is replaced by the inorganic titanium source of the same amount, its morphology changes from a regular sphere to an irregular nanoparticle morphology, which illustrates the important role of the organic titanium source on the crystal purity and morphology.
[0089] Comparative Example 2
[0090] A method for preparing an electrode material comprises the following steps:
[0091] S1. 0.4 mmol of ammonium dihydrogen phosphate, 0.27 mmol of ferrous oxalate, 0.03 mmol of tetraethyl titanate, 0.2 mmol of sodium carbonate, and 0.01 mmol of glucose were dissolved and dispersed in a mixed solvent consisting of 100 mL of ethanol and deionized water (wherein the volume ratio of deionized water to ethanol was 1:1), and the obtained mixture was mechanically ball-milled for 10 h to obtain a slurry;
[0092] S2, directly drying the slurry obtained in step S1 in an oven to obtain a precursor;
[0093] S3. The precursor prepared in step S2 is heated at 700° C. for 2 h under argon protection to obtain a positive electrode material.
[0094] S4. Perform material characterization test on the electrode material prepared in step S3.
[0095] According to the data analysis of the test results, the following conclusions can be drawn: Figure 7 As shown, the electrode material prepared by mechanical ball milling instead of the hydrothermal synthesis step contains a relatively obvious iron-sodium impurity phase, and a pure phase NFPP positive electrode material cannot be obtained.
[0096] 2. Preparation of sodium ion batteries
[0097] Example 3
[0098] A sodium ion battery prepared based on a positive electrode material, wherein the preparation method comprises the following steps:
[0099] (1) Preparation of positive electrode sheets: The NFPP positive electrode material prepared in Example 1, the polyanion positive electrode material prepared in Comparative Example 1, and the electrode material prepared in Comparative Example 2 were used as positive electrode active materials to prepare three different positive electrode sheets. The specific method is as follows: the positive electrode material, binder (PVDF), and conductive agent (Super P) were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent to prepare a slurry by homogenization. The slurry was then applied on a carbon-containing aluminum foil with a scraper to a thickness of 19 μm. The sheet was vacuum dried at 150° C. for 8 h to obtain a sheet, which was then cut into discs with a diameter of 14 mm.
[0100] (2) Preparation of sodium ion battery: The button cell method was used for testing. The positive electrode sheet prepared in step (1) was used to prepare the sodium ion battery. The assembly order of the battery components was: negative electrode shell-gasket-sodium sheet-glass fiber separator-positive electrode sheet-positive electrode shell; the electrolyte was 1 mol / L NaPF 6 , the solute is ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1).
[0101] 3. Performance testing
[0102] The specific conditions of the performance test are: 1.7~4.3V(vs.Na + / Na) voltage range, 0.5C (1C = 129mAh g -1 ) current conditions, constant current charge and discharge tests were carried out on the target material.
[0103] The specific steps include:
[0104] (1) The sodium ion battery prepared from the polyanion cathode material obtained in Example 1 was subjected to rate performance tests at 0.1C, 0.5C, and 1C. The test results are as follows: Figure 8 shown.
[0105] according to Figure 8 The data analysis in can draw the following conclusions:
[0106] The synthesized Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 The (NFPP) positive electrode material has reversible specific capacities of 98.84, 95.53, and 92.5 mAh / g at 0.1C, 0.5C, and 1C, respectively, and the first coulombic efficiency can reach 91.88%, showing excellent rate performance.
[0107] (2) The sodium ion battery prepared from the polyanion cathode material obtained in Comparative Example 1 was subjected to a rate performance test at 0.5C. The test results are as follows: Fig. 9 shown.
[0108] according to Fig. 9 The data analysis can draw the following conclusions:
[0109] The synthesized material was tested at a rate of 0.5C, and the reversible specific capacity was only 59.88 mAh / g, and the first coulombic efficiency was only 58.94%, showing low reversible specific capacity and performance.
[0110] (3) The electrochemical performance of the sodium ion battery prepared with the positive electrode material obtained in Comparative Example 2 was tested. The test results are as follows: Fig.10 shown.
[0111] according to Fig.10 The data analysis can draw the following conclusions:
[0112] The synthesized materials were tested at rates of 0.1C, 0.5C, and 1C, and the reversible specific capacities were 89.60, 61.29, and 41.20 mAh / g, respectively. The first coulombic efficiency could reach 88.62%, showing lower reversible specific capacity and performance.
[0113] Based on the data analysis of the test results, the following conclusion can be drawn: the electrochemical performance of this electrode material is poor.
[0114] In summary, the polyanion cathode material and its preparation method and application provided by the embodiments of the present invention, wherein in the preparation method, the organic titanium compound or the polymer of the organic titanium compound as a titanium source mainly acts as an in-situ dopant, morphology regulator and titanium source. The prepared polyanion cathode material has excellent electrochemical properties and has strong scalability and application value.
[0115] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0116] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a polyanion positive electrode material, characterized in that: include: In a solvent, an iron source, a phosphorus source, a sodium source, a titanium source and a carbon source undergo a hydrothermal reaction, and the reaction product is freeze-dried to prepare a precursor; Under the protection of an inert gas, the precursor undergoes a carbonization reaction to prepare a polyanion positive electrode material; Wherein, the titanium source is selected from organic titanium compounds or polymers of organic titanium compounds.
2. The preparation method according to claim 1, characterized in that: Among the iron source, phosphorus source, sodium source, titanium source and carbon source, the molar ratio of iron element, phosphorus element, sodium element, titanium element and carbon element is (2.7-2.95):4:(4-4.3):(0.05-0.3):(0.4-0.8).
3. The preparation method according to claim 1 or 2, characterized in that: The general formula of the organic titanium compound is shown in formula (I): Wherein, R1, R2, R3, and R4 are each independently selected from substituted or unsubstituted C2-C10 hydrocarbon groups; Alternatively, the organic titanium compound is titanium acetylacetonate.
4. The preparation method according to claim 3, characterized in that: R1, R2, R3, and R4 are each independently selected from butyl, isopropyl, tert-butyl, Ethyl.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The titanium source includes at least one of tetrabutyl titanate, tetraisopropyl titanate, titanium acetylacetonate, titanium tert-butoxide, isopropyl tri(dioctylphosphoyloxy) titanate, tetrabutyl titanate tetramer, di(triethanolamine) diisopropyl titanate, and tetraethyl titanate.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The iron source includes at least one of ferrous oxalate and ferrous chloride; And / or, the phosphorus source includes at least one of ammonium dihydrogen phosphate and sodium dihydrogen phosphate; And / or, the carbon source includes at least one of glucose, sucrose and fructose; And / or, the sodium source includes at least one of sodium carbonate, sodium oxalate and sodium acetate.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the hydrothermal reaction is 120-260°C and the time is 6-36h; And / or, the carbonization reaction temperature is 520-1000°C and the time is 4-12h; And / or, the solvent comprises at least one of a binary mixture of alcohol and water and a binary mixture of ketone and water; Preferably, the alcohol includes at least one of methanol, ethanol and butanol, and the ketone is acetone.
8. A polyanion positive electrode material, characterized in that: The polyanion positive electrode material is obtained by the preparation method according to any one of claims 1 to 7; The content of titanium element in the polyanion positive electrode material is 1-10%.
9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the polyanion positive electrode material according to claim 8.
10. An electrochemical energy storage device, characterized in that: The electrochemical energy storage device comprises the positive electrode sheet as claimed in claim 9.